Synthesis of silica-rich zeolite using quaternary ammonium-based templates. (April 2020) - Sriatun, S; Susanto, H; Widayat, W; Darmawan, A; Sriyanti, S; Kurniasari, R; Kurniawati, R
Abstract: In this study, silica-rich zeolite was made at a ratio Si/Al = 30. The template used was cationic surfactant from quaternary ammonium, tetrapropylammonium bromide (TPAB) and cetyltrimethylammonium bromide (CTAB). The CMC for TPABr (n – C3 H7 )4N is 10 −3 M, and spherical micelle of CTAB is 8.9x10 −4 M. The concentration of the TPAB and CTAB which used in this study were 0.0325; 0.125; 0.25 and 0.5 M. The results show that the type of synthesized zeolites are silica-rich sodalite with the crystal size 216 A°. The use of quaternary ammonium-based templates can increase crystallinity and reduce the size of silica-rich sodalite crystal grains but remain in the mesopore material size range. The concentration of the tetrapropylammonium bromide (TPAB) template is very influential on surface area and pore volume, whereas for cetyltrimethylammonium bromide (CTAB) it affects surface area but not on pore volume. The largest surface area and pore volume of 96 m 2 /g and 3.4×10 −2 obtained for silica-rich sodalite using a landfill template at small concentrations.